Needs Analysis of E-Flipbook as Digital Literacy Media in Conservation Biology Learning - Pertiwi Indah Lestari; Rizki Amalia Nur (Postgraduate, University of Mataram, 2023)
The purpose of this study was to analyse the level of need for learning resources or teaching materials for students in the Digital Age and to find out opportunities for media development with e-flipbooks in learning that can be used as a source of digital literacy. This research is descriptive research with a survey method. Descriptive research is used to understand and obtain a picture that occurs in the field as it is without making changes or interventions to the research target. The results of interviews and questionnaires of students and lecturers stated that a digital-based literacy media is needed that can increase student learning independence and can eliminate student boredom in learning including the development of e-flipbook teaching materials. In addition, lecturers and students need a digital-based literacy media in Conservation Biology Learning